2018
DOI: 10.1063/1.5044529
|View full text |Cite
|
Sign up to set email alerts
|

Development of an ion beam detector for the atomic beam probe diagnostic

Abstract: The atomic beam probe diagnostic concept aims at measuring the edge magnetic field and through that edge current distribution in fusion plasmas by observing trajectories of an ion beam stemming from a diagnostic neutral beam. The diagnostic potentially has microsecond scale time resolution and can thus prove to be a powerful option to study fast changes in the edge plasma. A test detector has been installed on the COMPASS tokamak as an extension of the existing lithium beam diagnostic system. It employs a rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Previous measurements 20 showed that electrons and ions as well as UV radiation reaching any metallic surface induce secondary electrons which make the measurement hard to interpret. The detector plate has to be masked so that the ions can only reach the detector at the Fara- day cups.…”
Section: B Detector Maskmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous measurements 20 showed that electrons and ions as well as UV radiation reaching any metallic surface induce secondary electrons which make the measurement hard to interpret. The detector plate has to be masked so that the ions can only reach the detector at the Fara- day cups.…”
Section: B Detector Maskmentioning
confidence: 99%
“…(30 keV, Li, 0.4 T homogenous field, 2 cm path in the field, r L =16 cm, deflection: 2.5 mm, 7 • ) The major difference of the setup described in Ref. 20 is that the magnetic field was less homogenous at the detector position which is indicated with a blue line in Figure 7. Figure 8 shows the Computer-Aided Design (CAD) model with one magnet and the covering mask removed (a), the full setup with the vacuum flange (b) and the detector head with the magnet holder zoomed (c).…”
Section: B Detector Holdermentioning
confidence: 99%
See 3 more Smart Citations